The antioxidant and anti-inflammatory activities of avasopasem manganese in age-associated, cisplatin-induced renal injury - Mapuskar, Kranti A.; Pulliam, Casey F.; Tomanek-Chalkley, Ann; Rastogi, Prerna; Wen, Hsiang; Dayal, Sanjana; Griffin, Benjamin R.; Zepeda-Orozco, Diana; Sindler, Amy L.; Anderson, Carryn M.; Beardsley, Robert; Kennedy, Eugene P.; et al. (Redox biology, 2024)
Cisplatin contributes to acute kidney injury (AKI) and chronic kidney disease (CKD) that occurs with greater frequency and severity in older patients. Age-associated cisplatin sensitivity in human fibroblasts involves increased mitochondrial superoxide produced by older donor cells. Young and old C57BL/6 J murine models of cisplatin-induced AKI and CKD were treated with the SOD mimetic avasopasem manganese to investigate the potential antioxidant and anti-inflammatory effects. Adverse event reporting from a phase 2 and a phase 3 randomized clinical trial (NCT02508389 and NCT03689712) conducted in patients treated with cisplatin and AVA was determined to have established the incidence and severity of AKI. Cisplatin-induced AKI and CKD occurred in all mice, however, was more pronounced in older mice. AVA reduced cisplatin-induced mortality, AKI, and CKD, in older animals. AVA also alleviated cisplatin-induced alterations in mitochondrial electron transport chain (ETC) complex activities and NADPH Oxidase 4 (NOX4) and inhibited the increased levels of the inflammation markers, TNFα, IL1, ICAM-1, and VCAM-1. Analysis of age-stratified subjects treated with cisplatin from clinical trials (NCT02508389, NCT03689712) also supported that the incidence of AKI increased with age and AVA reduced age-associated therapy-induced adverse events (AE), including hypomagnesemia, increased creatinine, and AKI. Older mice and humans are more susceptible to cisplatin-induced kidney injury, and treatment with AVA mitigates age-associated damage. Mitochondrial ETC and NOX4 activities represent sources of superoxide production contributing to cisplatin-induced kidney injury, and pro-inflammatory cytokine production and endothelial dysfunction may also be increased by superoxide formation.